Spin-dependent zero-bias peak in a hybrid nanowire-quantum dot system: Distinguishing isolated Majorana fermions from Andreev bound states - Ricco, L. S. [UNESP]; De Souza, M. [UNESP]; Figueira, M. S.; Shelykh, I. A.; Seridonio, A. C. [UNESP] (American Physical Society (APS), 2019)
A hybrid system composed by a semiconducting nanowire with proximity-induced superconductivity and a quantum dot at the end working as a spectrometer was recently used to quantify the so-called degree of Majorana nonlocality [M.-T. Deng Phys. Rev. B 98, 085125 (2018)2469-995010.1103/PhysRevB.98.085125]. Here we demonstrate that the spin-resolved density of states of the dot responsible for the zero-bias conductance peak strongly depends on the separation between the Majorana bound states and their relative couplings with the dot and investigate how the charging energy affects the spectrum of the system in the distinct scenarios of Majorana nonlocality (topological quality). Our findings suggest that the spin-resolved spectroscopy of the local density of states of the dot can be used as a powerful tool for discriminating between different scenarios of the emergence of the zero-bias conductance peak.